RANCANG-BANGUN SISTEM FLIGHT-RECORDER SEDERHANA UNTUK PELUNCURAN ROKET - Widada, Wahyu (Indonesian Journal of Aerospace, 2004)
In the rocket launch campaign, the telemetry system is very important system in order to send various data from the sensor to the base-station. However the signal of telemetry is not usually in good condition, and the data is very dificult to analyze. In this paper described the method to backup the sensor data by use of flight-recorder. It was very useful if the recovery of payload was successful, and the data flight can be analyze. The system used 2 wire serial eeprom with 131.071 byte of memory and 6 input for analog channels. The speed recording was 10 ms or 100 data per second.